2013
DOI: 10.1039/c3an01441j
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity liquid phase measurements using broadband cavity enhanced absorption spectroscopy (BBCEAS) featuring a low cost webcam based prism spectrometer

Abstract: Cavity enhanced techniques enable high sensitivity absorption measurements in the liquid phase but are typically more complex, and much more expensive, to perform than conventional absorption methods. The latter attributes have so far prevented a wide spread use of these methods in the analytical sciences. In this study we demonstrate a novel BBCEAS instrument that is sensitive, yet simple and economical to set up and operate. We use a prism spectrometer with a low cost webcam as the detector in conjunction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…Fielder et al [21] made the first demonstration of liquid-phase BBCEAS whilst Seetohul et al [17] reported the first HPLC-BBCEAS measurements. Qu et al [20] made BBCEAS measurements using a simple low cost webcam based spectrometer. The sensitivity of the measurements in the present study compares favorably with all the previous studies showing that similar levels of sensitivity can be achieved in microtiter plates as in cuvettes.…”
Section: Methodsmentioning
confidence: 99%
“…Fielder et al [21] made the first demonstration of liquid-phase BBCEAS whilst Seetohul et al [17] reported the first HPLC-BBCEAS measurements. Qu et al [20] made BBCEAS measurements using a simple low cost webcam based spectrometer. The sensitivity of the measurements in the present study compares favorably with all the previous studies showing that similar levels of sensitivity can be achieved in microtiter plates as in cuvettes.…”
Section: Methodsmentioning
confidence: 99%
“…Qu et al 19 LED Cuvette 527 6.5 × 10 −5 8.5 × 10 −10 9.1 × 10 5 Seetohul et al 13 LED HPLC cell 556 1.9 × 10 −5 2.1 × 10 −9 1.1 × 10 5 Fiedler et al 20 LAMP Cuvette 607 2.0 × 10 −5 --This study LED Cuvette 554 5.1 × 10 −6 7.1 × 10 −11 9.4 × 10 4 studies and will have significantly higher sensitivity than conventional single pass absorbance instruments. We can also envisage further increases in the sensitivity of the CEA spectrometer by improving the approach for mirror alignment e.g.…”
Section: Studymentioning
confidence: 99%
“…[19]. Também é reportada a utilização dos softwares Labview [20], RSpec [3], e MATLAB [21]. Para aquisição de espectros ópticos instantâneos, excelentes para demonstrações rápidas, existe a opção de instalar o software livre Theremino Spectrometer [22].…”
Section: Figuraunclassified